Discharge of ballast residual sediments during de-ballasting procedures: A more realistic estimate of propagule pressure - Nathalie Simard; Andrea M. Weise; André Rochon; Elizabeta Briski; Hugh J. MacIsaac; Christopher W. McKindsey (Marine Pollution Bulletin, 2024)

Water resource development and sturgeon (Acipenseridae): state of the science and research gaps related to fish passage, entrainment, impingement and behavioural guidance - S. J. Cooke; J. J. Cech; D. M. Glassman; J. Simard; S. Louttit; R. J. Lennox; L. Cruz-Font; C. M. O’Connor (Reviews in Fish Biology and Fisheries, 2020)

Survey of primary care physicians’ views about breast and ovarian cancer screening for true BRCA1/2 non-carriers - S. Pelletier; G. Larouche; J. Chiquette; Z. El Haffaf; W. D. Foulkes; P. Hamet; J. Simard; M. Dorval (Journal of Community Genetics, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

Vertical partitioning between sister species of R hizopogon fungi on mesic and xeric sites in an interior D ouglas‐fir forest - Kevin J. Beiler; Suzanne W. Simard; Valerie LeMay; Daniel M. Durall (Molecular Ecology, 2012)
Understanding ectomycorrhizal fungal ( EMF ) community structure is limited by a lack of taxonomic resolution and autecological information. R hizopogon vesiculosus and R hizopogon vinicolor ( B asidiomycota) are morphologically and genetically related species. They are dominant members of interior D ouglas‐fir ( P seudotsuga menziesii var . glauca ) EMF communities, but mechanisms leading to their coexistence are unknown. We investigated the microsite associations and foraging strategy of individual R . vesiculosus and R . vinicolor genets. Mycelia spatial patterns, pervasiveness and root colonization patterns of fungal genets were compared between R hizopogon species and between xeric and mesic soil moisture regimes. R hizopogon spp. mycelia were systematically excavated from the soil and identified using microsatellite DNA markers. R hizopogon vesiculosus mycelia occurred at greater depth, were more spatially pervasive, and colonized more tree roots than R . vinicolor mycelia. Both species were frequently encountered in organic layers and between the interface of organic and mineral horizons. They were particularly abundant within microsites associated with soil moisture retention. The occurrence of R . vesiculosus shifted in the presence of R . vinicolor towards mineral soil horizons, where R . vinicolor was mostly absent. This suggests that competition and foraging strategy may contribute towards the vertical partitioning observed between these species. R hizopogon vesiculosus and R . vinicolor mycelia systems occurred at greater mean depths and were more pervasive in mesic plots compared with xeric plots. The spatial continuity and number of trees colonized by genets of each species did not significantly differ between soil moisture regimes.

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Species patterns in foliar nitrogen concentration, nitrogen content and 13C abundance for understory saplings across light gradients - J. M. Kranabetter; S. W. Simard; R. D. Guy; K. D. Coates (Plant and Soil, 2010)

Do escaped transgenes persist in nature? The case of an herbicide resistance transgene in a weedy Brassica rapa population - S. I. WARWICK; A. LÉGÈRE; M.‐J. SIMARD; T. JAMES (Molecular Ecology, 2008)
The existence of transgenic hybrids resulting from transgene escape from genetically modified (GM) crops to wild or weedy relatives is well documented but the fate of the transgene over time in recipient wild species populations is still relatively unknown. This is the first report of the persistence and apparent introgression, i.e. stable incorporation of genes from one differentiated gene pool into another, of an herbicide resistance transgene from Brassica napus into the gene pool of its weedy relative, Brassica rapa , monitored under natural commercial field conditions. Hybridization between glyphosate‐resistant [herbicide resistance (HR)] B. napus and B. rapa was first observed at two Québec sites, Ste Agathe and St Henri, in 2001. B. rapa populations at these two locations were monitored in 2002, 2003 and 2005 for the presence of hybrids and transgene persistence. Hybrid numbers decreased over the 3‐year period, from 85 out of ~200 plants surveyed in 2002 to only five out of 200 plants in 2005 (St Henri site). Most hybrids had the HR trait, reduced male fertility, intermediate genome structure, and presence of both species‐specific amplified fragment length polymorphism markers. Both F 1 and backcross hybrid generations were detected. One introgressed individual, i.e. with the HR trait and diploid ploidy level of B. rapa, was observed in 2005. The latter had reduced pollen viability but produced ~480 seeds. Forty‐eight of the 50 progeny grown from this plant were diploid with high pollen viability and 22 had the transgene (1:1 segregation). These observations confirm the persistence of the HR trait over time. Persistence occurred over a 6‐year period, in the absence of herbicide selection pressure (with the exception of possible exposure to glyphosate in 2002), and in spite of the fitness cost associated with hybridization.

Metallogeny of the Mont-de-l’Aigle IOCG deposit, Gaspé Peninsula, Québec, Canada - M. Simard; G. Beaudoin; J. Bernard; A. Hupé (Mineralium Deposita, 2006)

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

PCNA Up-Regulation in Cerebral Vessels with Angiotensin II-Hypertension: Abnormal Regulation of Ca2+ Channel and Nitrate Tolerance Associated with Alternative Splicing of cGKI - A. Ivanov; S. Ivanova; L. V. Melnitchenko; V. Gerzanich; M. F. Shuba; J. M. Simard (Neurophysiology, 2003)

Genetic Determinants of Pseudomonas aeruginosa Colonization in Cystic Fibrosis Patients in Canada - M. De Braekeleer; C. Allard; J.-P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genetic determinants ofPseudomonas aeruginosa colonization in cystic fibrosis patients in Canada - M. Braekeleer; C. Allard; J. -P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Synthetic peptides corresponding to the F protein of RSV stimulate murine B and T cells but fail to confer protection - M. Trudel; E. J. Stott; G. Taylor; D. Oth; G. Mercier; F. Nadon; C. Séguin; C. Simard; M. Lacroix (Archives of Virology, 1991)